187 Variation in training: Results from a survey of UK neurology trainees. Issue 6 (27th May 2022) - Ross Russell, Amy L; Zarkali, Angeliki; Shribman, Samuel; Alexander, Sian K; Warner, Thomas T; Jones, Matthew; Pereira, Anthony; Hughes, Tom AT; Kipps, Christopher; Mummery, Catherine J
Abstract : Background: Neurology training in the UK is governed by a national curriculum defining the outcomes every trainee must achieve. However, the delivery of neurology training and trainee satisfaction differs significantly across the UK1. The Association of British Neurologists Trainees (ABNT) recently completed a qualitative study of the highest and lowest performing trusts for neurology training across the UK and identified key indicators associated with trainee satisfaction2. Aim: To establish the variation in these indicators across the country. Methods: We conducted a survey of UK neurology trainees to audit regional performance against the indicators identified in the previous qualitative study. Results: We had responses from 50 trainees, covering all deaneries. There was consultant supervision reported >98% of the time. 56% of supervising consultants were on-site during working hours, and 66% were present during clinics. In 74% of cases, the supervising consultant for inpatient referrals also had pre-booked clinics. Adaptation of daily roles according to trainee level was only reported by 26% of trainees, with <20% reponses reporting variation in clinic lists, or examples of ST3 shadowing. 52% of trainees were required to relocate during training. There was significant variation within deaneries, suggesting these factors are often determined at a trust level. 1. Shribman S, Alexander SK, Zarkali A, et al. doi:10.1136/practneurol-2018–002129 amyrossrussell@gmail.com